Patient’s Desire and Real Availability Concerning Supportive Measures Accompanying Radical Prostatectomy: Differences between Certified Prostate Cancer Centers and Non-Certified Centers Based on Patient-Reported Outcomes within the Cross-Sectional Study Improve - Wolff, Ingmar; Burchardt, Martin; Peter, Julia; Thomas, Christian; Sikic, Danijel; Fiebig, Christian; Promnitz, Sören; Hoschke, Bernd; Burger, Maximilian; Schnabel, Marco J.; Gilfrich, Christian; Löbig, Niklas; et al. (Cancers, 2023)
Certification as a prostate cancer center requires the offer of several supportive measures to patients undergoing radical prostatectomy (RP). However, it remains unclear how patients estimate the relevance of these measures and whether the availability of these measures differs between certified prostate cancer centers (CERTs) and non-certified centers (NCERTs). In 20 German urologic centers, a survey comprising questions on the relevance of 15 supportive measures was sent to 1000 patients at a median of 15 months after RP. Additionally, patients were asked to rate the availability of these measures using a four-item Likert scale. The aim of this study was to compare these ratings between CERTs and NCERTs. The response rate was 75.0%. In total, 480 patients underwent surgery in CERTs, and 270 in NCERTs. Patients rated 6/15 supportive measures as very relevant: preoperative medical counselling concerning treatment options, a preoperative briefing answering last questions, preoperative pelvic floor exercises (PFEs), postoperative PFEs, postoperative social support, and postoperative rehabilitation addressing physical fitness recovery. These ratings showed no significant difference between CERTs and NCERTs (p = 0.133–0.676). In addition, 4/9 of the remaining criteria were rated as more detailed by patients in CERTs. IMPROVE represents the first study worldwide to evaluate a patient-reported assessment of the supportive measures accompanying RP. Pertinent offers vary marginally between CERTs and NCERTs.
CRIS-Team Scopus Importer:2023-06-09
Keywords: certified prostate cancer centers; patient-reported outcome; perioperative supportive measures; prostate cancer; radical prostatectomy; survey